Correlation Between Body Mass Index and Anterolateral Thigh Flap Thickness: A Retrospective Study From a Single Center in China - Yin, Jianxin; Wang, Lei; Yang, Gongxin; Qin, Xingjun; Xiong, Ping (Frontiers in Surgery, 2021)
Background: During repair of oral and maxillofacial soft tissue defects, organ function is largely related to the amount of thickness of the flap. However, there are few studies on the influencing factors of the thickness of the flap. In this retrospective study, we aim to explore the correlation between BMI and ALT flap thickness by computed tomography (CT) and ultrasound and provide guidance for evaluating the ALT flap thickness before surgery. Methods: We selected three points A, B, and C on ALT flap and two skilled clinicians measured the thickness of these points. Age and gender as covariates and evaluated by the Chi-square analysis. Inter-group differences between the two BMI groups were examined by the student t test. Intra-group differences within each BMI group were tested by ANOVA. Linear regression analysis was performed to examine the relationship between BMI and ALT flap thickness. Results: 160 patients measured by CT were included in this study, and the ALT flap thickness measured by CT were 8.96 mm and 11.00 mm (P < 0.0001, t test) at point B in groups with BMI < 24.0 and BMI ≥ 24.0, respectively. The thicknesses at points A, B, and C were significantly correlated with the BMI (P < 0.001, correlation analysis, r = 0.462, 0.372, and 0.349 at the points A, B, and C, retrospectively, Pearson test). Conclusion: There was a significant correlation between the ALT flap thickness and BMI. To a certain extent, ultrasound could replace CT for measuring the ALT flap thickness.